Study of health status of street children in Khammam City of Andhra Pradesh - Berad, Aditya Suryabhan; Momula, Sampat; P, Ravi Kumar B (International Journal of Research in Medical Sciences, 2017)
Background: The objective was to study the health status of the street children in Khammam city and to study the socio-cultural environment of the street children in Khammam city. Methods: Type of study: A prospective and descriptive study. Study Population: All the street children in the city who are less than 18 years of age. 3Sample size: out of total 384 street children in the city, 150 were included in the study. Selection criteria: Children in different age groups of both sexes were selected. A total of 150 street children were included in the study. Data regarding socio-cultural environment and health status was collected by using pretested structured questionnaire after obtaining proper consent. Results: A total of 150 street children were interviewed (Males 86 and females 64). The mean duration of stay on street was 5.31 years. Nearly 10% of children were illiterate. The overall personal hygiene of the children was very bad. 97 (64.7%) children were malnourished. 6.7% of children had scabies. 30.66% children were anaemic. 46% children had Vit A deficiency. 17.33% children had Vit B deficiency. 34.7% children had visual problems. 18.66% children had ear and hearing problems. 60.66% of children had dental problems. 5.3% children had some psychiatric problems. 42.66% children had various addictions. Conclusion: There is an urgent need of coordination among development agents working for the rights of street children and information sharing among all stakeholders to enhance implementation strategies.